2D-speckle tracking right ventricular strain to assess right ventricular systolic function in systolic heart failure. Analysis of the right ventricular free and posterolateral walls. (15th October 2017) - Mouton, Stéphanie; Ridon, Héléne; Fertin, Marie; Pentiah, Anju Duva; Goémine, Céline; Petyt, Grégory; Lamblin, Nicolas; Coisne, Augustin; Foucher-Hossein, Claude; Montaigne, David; de Groote, Pascal
Abstract: Background: Right ventricular (RV) systolic function is a powerful prognostic factor in patients with systolic heart failure. The accurate estimation of RV function remains difficult. The aim of the study was to determine the diagnostic accuracy of 2D-speckle tracking RV strain in patients with systolic heart failure, analyzing both free and posterolateral walls. Methods: Seventy-six patients with dilated cardiopathy (left ventricular end-diastolic volume ≥ 75 ml/m 2 ) and left ventricular ejection fraction ≤ 45% had an analysis of the RV strain. Feasibility, reproducibility and diagnostic accuracy of RV strain were analyzed and compared to other echocardiographic parameters of RV function. RV dysfunction was defined as a RV ejection fraction ≤ 40% measured by radionuclide angiography. Results: RV strain feasibility was 93.9% for the free-wall and 79.8% for the posterolateral wall. RV strain reproducibility was good (intra-observer and inter-observer bias and limits of agreement of 0.16 ± 1.2% [− 2.2–2.5] and 0.84 ± 2.4 [− 5.5–3.8], respectively). Patients with left heart failure have a RV systolic dysfunction that can be unmasked by advanced echocardiographic imaging: mean RV strain was − 21 ± 5.7% in patients without RV dysfunction and − 15.8 ± 5.1% in patients with RV dysfunction (p = 0.0001). Mean RV strain showed the highest diagnostic accuracy to predict depressed RVEF (area under the curve (AUC) 0.75) with moderate sensitivity (60.5%) but high specificity (87.5%) using a cutoff value of − 16%. Conclusions: RV strain seems to be a promising and more efficient measure than previous RV echocardiographic parameters for the diagnosis of RV systolic dysfunction.